PEMANFAATAN SISTEM INFORMASI PENJUALAN UNTUK PROSES PENGOLAHAN DATA TRANSAKSI PENJUALAN RUMAH PADA PT.CIPTA ANUGERAH SEJATI CIREBON - Cucu Handayani; Uswatun Khasanah (LPPM Sekolah Tinggi Ilmu Ekonomi Cirebon, 2021)
Information systems in the business world are absolutely necessary, especially in the field of sales, where sales information systems and faster data processing can help the sales transaction service process, so as to optimize performance both in terms of time and in terms of costs. This study observes and analyzes the Sales System. Sales System Design is a sales program application that can be used to manage data with the latest information flow and process the storage and search of sales data according to company needs, using the home sales program application, it can help companies monitor sales progress made by the sales department. As well as the use of information technology / computers which are expected to provide solutions to problems that occur in the management of home sales transaction data at PT. Cirebon's True Award Creation.